2013
DOI: 10.1002/hed.23250
|View full text |Cite
|
Sign up to set email alerts
|

Novel DICER1 mutation as cause of multinodular goiter in children

Abstract: Background To present a rare case of an adolescent with multinodular goiter (MNG) found to have a DICER1 mutation. Methods Chart review including endocrine hormone tests, thyroid ultrasound, and genetic testing for DICER1. Results A 12-year-old female presented with a diffusely enlarged thyroid gland. Family history revealed an older sister with a history of bilateral ovarian Sertoli-Leydig cell tumors and MNG. Thyroid function tests were normal. Serial thyroid ultrasounds showed enlarging multiple bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In case 2, germline testing of the patient's blood‐derived DNA revealed a premature truncating mutation (c.1525C > T p.R509Ter) in DICER1 (Table 1). 19 We identified two distinct DICER1 hotspot mutations, c.5438A> C, p.E1813A and c.5113G> A, p.E1705K, in the left and right ovarian tumours, respectively (Table 1). 14 …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In case 2, germline testing of the patient's blood‐derived DNA revealed a premature truncating mutation (c.1525C > T p.R509Ter) in DICER1 (Table 1). 19 We identified two distinct DICER1 hotspot mutations, c.5438A> C, p.E1813A and c.5113G> A, p.E1705K, in the left and right ovarian tumours, respectively (Table 1). 14 …”
Section: Resultsmentioning
confidence: 91%
“…Patients with germline mutations have DICER1 syndrome. As well as SLCT, these patients are also predisposed to develop a wide range of other ‘hyperplastic’ disorders and uncommon neoplasms; these include lung cysts, thyroid multinodular goitre, various benign and malignant thyroid neoplasms, pleuropulmonary blastoma, cystic nephroma, anaplastic sarcoma of the kidney, ciliary body medulloepithelioma, nasal chondromesenchymal hamartoma, pituitary blastoma, pineoblastoma, and embryonal rhabdomyosarcoma of the cervix, ovary, fallopian tube, and genitourinary tract 9,12–20 …”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Rio Frio and coworkers (6) identified germline mutations in DICER1 (on chromosome 14q32) as the cause of familial MNG with or without ovarian Sertoli-Leydig cell tumor (SLCT) (7), adding a new phenotype to the DICER1 syndrome (OMIM #601200). Since then, several articles have reported patients with germline DICER1 mutations who have MNG alone or in combination with other known DICER1-related diseases (8,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In support of previous studies exploring rare exclusive MNG families, 11,20 we confirmed that MNG/TD occurring in children and young adults should be used to identify DICER1-syndrome families and to perform cascade testing, genetic counselling and implement preventive strategies. This requires a close collaboration between oncologists and endocrinologists, from paediatrics to adulthood, to determine the true prevalence of thyroid disease in this syndrome.…”
Section: Discussionmentioning
confidence: 99%